MOTIVASI ORANG TUA MEMASUKKAN ANAKNYA KE HOMESCHOOLING KAK SETO PEKANBAU - Lisari, Fenni Dwi; Maemunaty, Titi; ', Sumardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research background is what factors that cause parents registering their child to Homeschooling Kak Seto, Pekanbaru. The research problem was what is the dominant factors parents registering their children to homeschooling kak Seto whether instrinsic motivation or extrinsic motivation? The purpose of this research is to know the most dominant motivation that motivates parents to register their children to Homeschooling Kak Seto Pekanbaru. The populations in this research are 67 people. Then the sample this research was 47 people and 20 people of population would be the sample for testing validation questioniere. The sample technique used was Simple Random Sampling. The instruments of collecting data is questionnaire with 51 statements and after validating test of item, the number of items will be 35 statements. The data analisys used is the quantitative and descriptive approach. The result describes that mean score of motivation of Parents to register their children to homeschooling Kak Seto Pekanbaru is intrinsic motivation with mean score 4,2. It means that the intrinsic motivation has more influences rather than extrinsic motivation why parents registering their children to homeschooling Kak Seto Pekanbaru.Key words: Motivation, Homeschooling.